The landscape of Chinese open educational resources research. Issue 4 (2014) - ,; ,; ,
Abstract : Purpose – After the official definition of Open Educational Resources (OER) at the Forum on Open Courseware for Higher Education in Developing Countries in 2002, the concept was soon introduced to China and popularised among scholars, practitioners, and educators. After ten years of proliferation, it is important to explore the landscape of Chinese OER research. The paper aims to discuss these issues.Design/methodology/approach – This paper adopts social network analysis (SNA) to analyse the network defining the citations of 133 OER journal articles published in China.Findings – The findings illustrate that the academic circle of OER in China is small, which leads to restricted innovation. Most publications are produced by researchers working at comprehensive universities and normal universities (teachers colleges).Research limitations/implications – In these universities, a number of active OER researchers are emerging, but no OER research team can be identified from their citation networks. Currently, most OER research is still descriptive research, and only few case studies are being to gradually be conducted.Practical implications – As the Chinese OER research is still in the initial stage, more research projects in OER need to be explored to construct higher quality and more influential open content to achieve deep openness.Originality/value – In the literature, no one has adopted the SNA to analyse the citation network of Chinese OER research. Acknowledgements : The authors would like to thank Beijing Municipal Education Science Foundation (P R China) for financially supporting this research under Project No. CJA12135.